EVALUASI ALOKASI DANA DESA (ADD)TENTANG PENGHASILAN TETAP (SILTAP) KEPALA DESA DAN PERANGKAT DESA DI DESA KALISEMO KECAMATAN LOANO KABUPATEN PURWOREJO (Progress, 2024)
In the field of village administration, there is a budget regarding the Fixed Income of the Village Head and Village Officials, and there are allowances for BPD operations, Village Government Operational Expenditures and RT / RW Operations. This is a problem for village government officials, especially Kalisemo village, by making it one permanent income for the village head and village apparatus under one roof of the budget line, namely the allocation of village funds, so to be able to enjoy the salary, the village apparatus must wait for the ADD Budget disbursement first so that it cannot enjoy a quarter of a month's salary and even a month will only be a luxury and impossible. The purpose of this study was to determine ADD in Kalisemo Village, determine the suitability of the percentage of VillageHeads and Village Officials in Kalisemo Village, Loano District, Purworejo Regency to ADD, to know the implementation / application of ADD in Kalisemo Village About SILTAP Village Heads and Village Officials and to know Evaluation ADD regarding SILTAP of Village Heads and Village Officials in Kalisemo Village.In this research, the type of data used is qualitative data and quantitative data. The data sources are primary data, secondary data, information and analogical situations. The data source sampling technique used is social citation. The type of data collection used is observation, interviews / interviews, literature study and documentation. The data analysis techniques in this study were data reduction, data copy and drawing conclusions or verification. In data validation research or testing the validity of data is an important factor in research. This study uses a percentage technique with a formula. The data presentation technique uses descriptions and is qualitatively explained, analyzed through descriptive explanations. Meanwhile, the analyzed data will be presented in the form of tables and attachmentsVillage Fund Allocation in Kalisemo village, Loano sub-district is paid twice a year. In addition, the application of ADD regarding SILTAP for VillageHeads and Village Officials is set at a maximum limit of 60% of the total ADD. SILTAP of Village Heads and Village Officials in Kalisemo Village, Loano District, Purworejo Regency towards ADD according to the percentage of provisions that have been set, which is 60%. Implementation / application of ADD regarding SILTAP for Village Heads and Village Officials in Kalisemo Village that SILTAP in Kalisemo Village has met the maximum limit of 60% and implementation of ADD spending on SILTAP expenditure for Village Heads and Village Officials is implemented according to existing rules, namely the current SILTAP regulations so the one with ADD. Evaluation of the Accountability Report for the SILTAP report of the Village Head and Village Officials in Kalisemo Village is still lacking in completeness of the files. For attachments, a photocopy of Decree (SK) on the Amount of First Semester SILTAP Acceptance and a photocopy of the Decree of the Goods and Services Procurement Team, then a photocopy of the Decree of the Activity Implementation Team has not been attached to the Accountability report (LPJ). In carrying out work, the apparatus is not in accordance with the main duties and functions of each job.